2020
DOI: 10.1002/adhm.202001118
|View full text |Cite
|
Sign up to set email alerts
|

A Red Light‐Triggered Drug Release System Based on One‐Photon Upconversion‐Like Photolysis

Abstract: Photoresponsive drug release systems can enhance drug accumulation at the sites where light is applied. Nowadays, the photocleavable groups used in the systems usually require ultraviolet or blue light irradiation, which limits tissue penetration depth and is harmful to normal cells and living bodies. A one-photon upconversion-like photolysis strategy, which can cleave green light-activatable prodrugs with red light at the presence of a red light-excitable photosensitizer in organic solvents, is developed. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 33 publications
(53 reference statements)
0
29
0
Order By: Relevance
“…The result can be explained by the fact that some byproducts were generated during the photocleavage reaction and the released Cb was not stable in aqueous solutions (Figure S6). 20,34,37 These results demonstrated that IR783/BC NPs exhibited both good stability in the dark and excellent photocleavable ability upon light irradiation, confirming their potency for photoresponsive drug delivery.…”
Section: Results and Disscussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The result can be explained by the fact that some byproducts were generated during the photocleavage reaction and the released Cb was not stable in aqueous solutions (Figure S6). 20,34,37 These results demonstrated that IR783/BC NPs exhibited both good stability in the dark and excellent photocleavable ability upon light irradiation, confirming their potency for photoresponsive drug delivery.…”
Section: Results and Disscussionmentioning
confidence: 72%
“…Recently, photoresponsive prodrugs have been developed with tailor‐made structures containing photocleavable moieties such as coumarin and boron‐dipyrromethene (BODIPY) for photoactivable chemotherapy 17–19 . For instance, BODIPY‐chlorambucil (BC) prodrug, of which the BODIPY group can be efficiently cleaved upon light irradiation, was developed and achieved effective antitumor effect with the utilization of laser light 20 . However, due to the hydrophobicity of most photocleavable groups, water solubility of the reported photoresponsive prodrugs is generally poor, which hindered their utility in vivo 21,22 …”
Section: Introductionmentioning
confidence: 99%
“…[ 9 , 10 ] Among the various strategies, light activation has demonstrated to be a promising option, by which the release of bioactive molecules can be readily controlled with high spatiotemporal precision. [ 11 , 12 , 13 , 14 , 15 ] Nevertheless, the currently used photocleavable groups in such systems usually require ultraviolet (UV) or blue light irradiation, which exhibited potential light‐induced toxicity and low penetrating ability. [ 16 ] Compared with other tissues, the transparent vitreous body can be efficiently penetrated by light, which provides excellent potentials for light‐triggered drug delivery systems in the treatment of eye diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Such process requires oxygen-free environment to maximize the photolysis efficiency because oxygen can hinder TTET by quenching the excited triplet states of prodrug or photosensitizer. A further study on a polymeric PLA-PEG nanocarrier encapsulating prodrug and photosensitizer enabled red light-triggered prodrug photolysis in normoxia conditions [ 21 ]. However, the type of drugs that can be used in the system is limited, since the synthesis of light-responsive prodrugs requires the drugs to contain certain functional groups (e.g., carboxyl group).…”
Section: Introductionmentioning
confidence: 99%